2003
DOI: 10.1002/jnr.10587
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells enhance differentiation of cocultured neurosphere cells and promote regeneration of injured spinal cord

Abstract: Transplantation of bone marrow stromal cells (MSCs) has been regarded as a potential approach for promoting nerve regeneration. In the present study, we investigated the influence of MSCs on spinal cord neurosphere cells in vitro and on the regeneration of injured spinal cord in vivo by grafting. MSCs from adult rats were cocultured with fetal spinal cord-derived neurosphere cells by either cell mixing or making monolayered-feeder cultures. In the mixed cell cultures, neuroshpere cells were stimulated to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(158 citation statements)
references
References 47 publications
2
155
1
Order By: Relevance
“…73 Chopp et al 74 found that intramedullary transplantation of MSCs 1 week after spinal cord injury improved functional outcome over a 5-week period, with a few cells expressing neural markers. Wu et al 75 also showed functional recovery after MSC transplantation at the time of injury and attributed this to enhanced differentiation of endogenous neural stem cells as indicated by in vitro coculture experiments. In contrast, Hofstetter et al 76 observed functional recovery only when MSCs were transplanted in a delayed fashion after 1 week, and suggested that the strands formed by MSCs may provide axon guidance to explain the improvement rather than cellular replacement.…”
Section: Nonhuman Mscsmentioning
confidence: 93%
“…73 Chopp et al 74 found that intramedullary transplantation of MSCs 1 week after spinal cord injury improved functional outcome over a 5-week period, with a few cells expressing neural markers. Wu et al 75 also showed functional recovery after MSC transplantation at the time of injury and attributed this to enhanced differentiation of endogenous neural stem cells as indicated by in vitro coculture experiments. In contrast, Hofstetter et al 76 observed functional recovery only when MSCs were transplanted in a delayed fashion after 1 week, and suggested that the strands formed by MSCs may provide axon guidance to explain the improvement rather than cellular replacement.…”
Section: Nonhuman Mscsmentioning
confidence: 93%
“…A number of different cell types have been evaluated; these include adult mesenchymal stem cells derived from the bone marrow (MSC). MSC have been shown to promote anatomical and functional recovery in animal models of SCI by promoting tissue sparing (Himes et al, 2006;Sheth et al, 2008), and axonal regeneration (Wu et al, 2003). The therapeutic benefits of MSC are thought to be primarily related to their secretion of soluble factors and the provision of an extracellular matrix that provides neural protection and support, and secondarily to remyelination (Akiyama et al, 2002a(Akiyama et al, ,2002b, and neural differentiation (Ankeny et al, 2004;Zurita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrast, BMSCs, belonging to autologous grafts and have the advantages of safty, no ethically problematic issue and that immumnosuppression is not necessary. In addition, BMSCs are known to secrete a substantial amount of neurotrophic factors and cytokines into the soluble stroma and provide a supportive microenvironment for both the growth and differentiation of the hematopoietic stem cells in vivo and in vitro [9,10,21,22] . In the past years, Ye et al have proven that BMSCs can secret GDNF but the amount was very low [11] (< 100 pg/mL), which is not enough to protect the damaged neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Titer of the lentiviral stock was determined by: Number of clonies × Folds of dilution (TU/ mL). [9,10] Bone marrow was isolated under sterile conditions from 8-weekold male Sprague-Dawley rats. Donor rats were killed by cervical dislocation, and the tibias were dissected.…”
Section: Construction Of Expressing Vector Plenti6/v5-gdnfmentioning
confidence: 99%